2022
DOI: 10.1039/d1fo04331e
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus LA85 ameliorates cyclophosphamide-induced immunosuppression by modulating Notch and TLR4/NF-κB signal pathways and remodeling the gut microbiota

Abstract: With the prevalence of coronavirus disease 2019 (COVID-19), we found that probiotics may be effective in organism immune recovery and remodeling of gut microbiota in their patients and recovered individuals....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“… 24 This is similar to the research results of Jia et al. 25 Of interest, Erysipelatoclostridium 26 and Butyricicoccus 27 have also been shown to promote intestinal mucosal repair. Norank_f__ Ruminococcaceae 27 , 28 and Roseburia 29 enhance intestinal barrier function by upregulating TJ protein expression, and have anti-inflammatory potential.…”
Section: Discussionsupporting
confidence: 85%
“… 24 This is similar to the research results of Jia et al. 25 Of interest, Erysipelatoclostridium 26 and Butyricicoccus 27 have also been shown to promote intestinal mucosal repair. Norank_f__ Ruminococcaceae 27 , 28 and Roseburia 29 enhance intestinal barrier function by upregulating TJ protein expression, and have anti-inflammatory potential.…”
Section: Discussionsupporting
confidence: 85%
“…66 CP also acts on tissue protein and affects tissue barrier integrity. 13,67 Thus, CP is potentially toxic even at non-lethal concentrations; toxicity is concentration dependent. 51 Recently, alterations in the biochemicals of Nile tilapia exposed to CP were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the body, aer medication, CP could induce oxidative stress. 67 It was reported that the CP exposure could decrease antioxidant ability in the tissues of sh (Oreochromis niloticus). 63 ) and defends cells from oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Another study used Lactobacillus acidophilus LA85 to increase the expression of MATH-1. 19 The high level of MATH-1 expression can be attributed to an increase in stem cell activity, which in turn can lead to an increase in the activity of the secretory precursor. 13…”
Section: Groupsmentioning
confidence: 99%